Influence of tillage systems and sowing dates on the incidence of leaf spot disease in Telfairia occidentalis caused by Phoma sorghina in Cameroon - Kebei Andrew Kpu; Mbong Grace Annih; Agyingi Lucy Ambang; Ebile Dayan Agwah (Scientific Reports, 2022)
Abstract The production and leaf quality of Telfairia occidentalis in Cameroon are gravely threatened by leaf spot disease. A field study was conducted in July 2019 and 2020 to determine the influence of tillage systems and sowing dates on the incidence of Telfairia occidentalis leaf spot caused by Phoma sorghina. A randomized block design with three replications and four planting dates was used. The soil physicochemical properties were also determined. Data for disease incidence were registered once every two weeks and submitted to generalized linear model for statistical analysis. The means were separated by Duncan’s multiple range test at a 95% confidence interval. Calculations for disease incidence and statistical analysis were conducted using the Microsoft Excel program and SPSS version 23, respectively. Statistical analysis revealed that the zero tilled field generally registered a lower leaf spot disease incidence than the tilled field, which was highly significant (p ≤ 0.05). In addition, the second sowing date in the zero tilled field proved to be better in terms of low disease incidence than other sowing dates employed in the study. Therefore, to minimize the devastating effects of leaf spot disease, zero tillage coupled with the second sowing date could be exploited.